2005
DOI: 10.1088/0953-8984/17/20/002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of gelling liquids: a short survey

Abstract: The dynamics of randomly crosslinked liquids is addressed via a Rouse-and a Zimm-type model with crosslink statistics taken either from bond percolation or Erdős-Rényi random graphs. While the Rouse-type model isolates the effects of the random connectivity on the dynamics of molecular clusters, the Zimm-type model also accounts for hydrodynamic interactions on a preaveraged level. The incoherent intermediate scattering function is computed in thermal equilibrium, its critical behaviour near the sol-gel transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 115 publications
(263 reference statements)
1
11
0
Order By: Relevance
“…On the other hand, if excluded-volume interactions were absent, the geometric fractal dimension d f would take on p-3 the Gaussian or ideal Rouse value d (G) f ≈ 4. The resulting lower bound for k would then coincide with the exact result in the phantom case that was computed previously [22][23][24].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, if excluded-volume interactions were absent, the geometric fractal dimension d f would take on p-3 the Gaussian or ideal Rouse value d (G) f ≈ 4. The resulting lower bound for k would then coincide with the exact result in the phantom case that was computed previously [22][23][24].…”
supporting
confidence: 77%
“…for the viscosity of the Rouse model for gelling polymers [22][23][24] in terms of the cluster-weighted sum of the squared radii of gyration…”
mentioning
confidence: 99%
“…The translational diffusion coefficient is a macroscopic transport coefficient, but DLS is actually a technique that records all types of motions excited by thermal fluctuations. If the measurements are made in the limit of small q values such that qR g < 1, the whole particle is seen. 11a On the other hand, scattering measurements made under conditions of qR g ≫ 2 probe distances in a particle which are much smaller than the particle diameter. For most colloidal particles there will be no difference in the result for the diffusion coefficient when the experiments are made at any angle.…”
Section: Theoretical Background Of Dynamic Light Scatteringmentioning
confidence: 99%
“…In contrast, macromolecules are composed of mostly flexible linear, branched, or cross-linked chains. Now, segmental modes of motion are superimposed upon the translational motion. 11a,b …”
Section: Theoretical Background Of Dynamic Light Scatteringmentioning
confidence: 99%
“…Besides, the major difference between the structures of dendrimer and Husimi cactus is that the former is a tree while the latter contains loops. The previous research showed that the existence of loops has strong correlation with the dynamics of polymer networks [54][55][56], so that we also analyze the influence of loop structure on trapping process by comparing the results of Husimi cactus with dendrimer.…”
Section: Introductionmentioning
confidence: 99%